Analysis of Marketing Aspects of Surabaya's Semicolic Point Cafe in A Sharia Perspective - M. Firdaus Tri Kuncoro; Abdul Rohman (Penerbit Hellow Pustaka, 2024)
Marketing is an important factor in achieving success for a business. Food is no longer just a necessity, but a lifestyle. The culinary world is growing rapidly with its uniqueness. Café Titik Koma utilizes business opportunities in the caffeshop sector in the city of Surabaya. Café Titik Koma has a target audience of young people. The management of the Titik Koma café is carried out by the owner, manager and employees who have generated large revenues. The purpose of this study was to identify the marketing mix at Café Titik Koma, by looking at the aspects of product mix, price, promotion and place. This is to determine the strength of the Titik Koma café using the 4P theory. This research uses qualitative research. The analysis used is descriptive qualitative. The research results obtained in this study are the 4P marketing mix theory at the Titik Koma cafe has been implemented well. It shows that the strength of Titik Koma café is in a varied and unique product mix, affordable prices, promotions using social media and a strategic place with adequate facilities. Based on the overall results of the research results, it is hoped that Café Titik Koma will emphasize more on promotions other than on Instagram by promoting on other social media. Café Titik Koma to always maintain taste, product quality and wifi facilities that support consumer convenience.